'Saving the lives of our dogs': the development of canine distemper vaccine in interwar Britain - Michael Bresalier (British Journal of the History of Science, 2014)
This paper examines the successful campaign in Britain to develop canine distemper vaccine between 1922 and 1933. The campaign mobilized disparate groups around the com- mon cause of using modern science to save the nation’s dogs from a deadly disease. Spearheaded by landed patricians associated with the country journal The Field, and funded by dog owners and associations, it relied on collaborations with veterinary professionals, government scientists, the Medical Research Council (MRC) and the commercial pharma- ceutical house the Burroughs Wellcome Company (BWC). The social organization of the campaign reveals a number of important, yet previously unexplored, features of interwar science and medicine in Britain. It depended on a patronage system that drew upon a large base of influential benefactors and public subscriptions. Coordinated by the Field Distemper Fund, this system was characterized by close relationships between landed elites and their social networks with senior science administrators and researchers. Relations between experts and non-experts were crucial, with high levels of public engagement in all aspects of research and vaccine development. At the same time, experimental and commercial research supported under the campaign saw dynamic interactions between animal and human medicine, which shaped the organization of the MRC’s research programme and demonstrated the value of close collaboration between veterinary and medical science, with the dog as a shared object and resource. Finally, the campaign made possible the translation of ‘laboratory’ findings into field conditions and commercial products. Rather than a unidirectional process, translation involved negotiations over the very boundaries of the ‘laboratory’ and the ‘field’, and what constituted a viable vaccine. This paper suggests that historians reconsider standard historical accounts of the nature of patronage, the role of animals, and the interests of landed elites in interwar British science and medicine.